1996
DOI: 10.1037/0021-9010.81.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Social exchange in organizations: Perceived organizational support, leader–member exchange, and employee reciprocity.

Abstract: Social exchange (P. Blau, 1964) and the norm of reciprocity (A. W. Gouldner, 1960) have been used to explain the relationship of perceived organizational support and leader-member exchange with employee attitudes and behavior. Recent empirical research suggests that individuals engage in different reciprocation efforts depending on the exchange partner (e.g., B. L. McNeely & B. M. Meglino, 1994). The purpose of the present study was to further investigate these relationships by examining the relative contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
706
7
16

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,527 publications
(813 citation statements)
references
References 63 publications
(82 reference statements)
27
706
7
16
Order By: Relevance
“…We argue that the attitudes formed on the basis of one or more negotiation counterparts in an employment negotiation spread, in turn, to satisfaction with one's job as a whole. Previous research has demonstrated that job satisfaction can result from the quality of employees' relationships with key individuals such as supervisors (Settoon, Bennett, & Liden, 1996;Yukl, 1989) or close friends at work (Winstead, Derlega, Montgomery, & Pilkington, 1995). We argue that incoming employees see their negotiation counterparts as representatives of their employing organizations and likely generalize from the relationship that they developed during the negotiation.…”
Section: Job Satisfactionmentioning
confidence: 77%
“…We argue that the attitudes formed on the basis of one or more negotiation counterparts in an employment negotiation spread, in turn, to satisfaction with one's job as a whole. Previous research has demonstrated that job satisfaction can result from the quality of employees' relationships with key individuals such as supervisors (Settoon, Bennett, & Liden, 1996;Yukl, 1989) or close friends at work (Winstead, Derlega, Montgomery, & Pilkington, 1995). We argue that incoming employees see their negotiation counterparts as representatives of their employing organizations and likely generalize from the relationship that they developed during the negotiation.…”
Section: Job Satisfactionmentioning
confidence: 77%
“…Indeed, LMX research has revealed that the quality of the relationship has a positive relationship with the frequency with which followers engage in activities beyond the employment contract (Liden & Graen, 1980;Settoon et al, 1996;Wayne & Green, 1993). However, as noted, estimates of the strength of the LMXcitizenship behavior relationship have varied considerably.…”
Section: Foundations Of the Lmx And Citizenship Behavior Relationshipmentioning
confidence: 99%
“…Citizenship behaviors are likely avenues for reciprocation because they reflect discretionary individual behavior that is less likely to be recognized by job descriptions or formal reward systems (Organ, 1988). In essence, subordinates in higher quality LMX relationships "pay back" their leaders by engaging in citizenship (i.e., discretionary) behaviors that benefit the leader and others in the work setting Settoon, Bennett & Liden, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
AbstractThis field study examines the joint effects of social exchange relationships at work (LMX:leader-member exchange and TMX: team-member exchange) and employee personality Existing research has demonstrated the importance of personality characteristics and social exchange relationships as predictors of task and citizenship performance (Barrick & Mount, 1991;Eisenberger, Fasolo, & Davis-LaMastro, 1990;Judge & Ilies, 2002;LePine & Van Dyne, 2001;Settoon, Bennett, & Liden, 1996). To date, however, consideration of personality characteristics and social exchange relationships as predictors of employee performance has been addressed in two predominantly separate literatures.
…”
mentioning
confidence: 99%